2011
DOI: 10.3892/ijmm.2011.659
|View full text |Cite
|
Sign up to set email alerts
|

Fasudil, a Rho-associated protein kinase inhibitor, attenuates retinal ischemia and reperfusion injury in rats

Abstract: Abstract. Abnormal activation of Rho kinase (ROcK) plays a vital role in the pathogenesis of ischemia/reperfusion (I/R)-induced retinal injury. The aim of this study was to investigate whether fasudil, a potent inhibitor of ROcK, has a protective effect on retinal I/R injury in rats and to explore the possible underlying mechanisms. Forty adult Sprague-dawley rats were randomly assigned into sham, I/R injury model (I/R), model plus normal saline (control), and model plus fasudil (fasudil) groups. Rats in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Such abnormal temporary phenomenon might be triggered by several factors. On one hand, ROCK inhibitors can interfere with the apoptotic Caspase 3-ROCK signalling pathway (Song and Gao, 2011), and, consequently, increase the number of viable cells. However, a more likely explanation is that as a response to treatment with toxins within certain time-window, cells tend to increase metabolism, which manifests itself as enhanced reduction of resazurin.…”
Section: Discussionmentioning
confidence: 99%
“…Such abnormal temporary phenomenon might be triggered by several factors. On one hand, ROCK inhibitors can interfere with the apoptotic Caspase 3-ROCK signalling pathway (Song and Gao, 2011), and, consequently, increase the number of viable cells. However, a more likely explanation is that as a response to treatment with toxins within certain time-window, cells tend to increase metabolism, which manifests itself as enhanced reduction of resazurin.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has demonstrated that administration of an oral ROCK inhibitor, K115, delayed RGC death [78]. Fasudil also resulted in ischemia-related apoptosis of retinal cells by inhibiting Bax/Bcl-2, caspase-3, and iNOS in rats [79]. However, the importance of ROCK for neural degeneration in vitreoretinal diseases including DR and AMD is unknown.…”
Section: Future Directions Of Rock Inhibitors: Neuroprotectionmentioning
confidence: 99%
“…149 R-1 , R-3 and R-4 have been further shown to protect RGCs from apoptosis. R-1 protects the retina of rats from both ischemia/reperfusion induced damage 150 and N-methyl-D-aspartate (NMDA) induced excitotoxicity. 151 In rats treated with R-4 , the number of RGCs with regenerating axons was increased.…”
Section: New Therapies In Late-stage Developmentmentioning
confidence: 99%